Efficient visible-light-driven water splitting performance of sulfidation-free, solution processed Cu2MgSnS4 thin films: Role of post-drying temperature. (June 2020) - Sharma, Akash; Sahoo, Pooja; Singha, Abhijit; Padhan, Subash; Udayabhanu, G.; Thangavel, R.
Graphical abstract: Highlights: We introduced a molecular ink based, sulfidation-free approach for fabrication of Cu2 MgSnS4 thin films. The photoelectrochemical performance of Cu2 MgSnS4 was investigated for the first time. Phase tunability form kesterite to stannite was observed with increase in post-drying temperature. Abstract: This report presents the fabrication of Cu2 MgSnS4 (CMTS) thin films by using sol–gel, spin coating technique without sulfurization process. The structural, morphological, optical and photoelectrochemical properties were systematically investigated with respect to the variation in post-drying temperature ranging from 250 to 400 °C. The XRD patterns indicates the formation of tetragonal structure. Also the crystallinity of the thin films has improved with the increase in temperature. The uniform morphology of the thin films were examined by FESEM images up to a processing temperature of 300 °C. But with increase in post-drying temperature cracks and pinholes appear on the films. From the absorbance results a decrease in the estimated bandgap values from 1.999 to 1.775 eV was observed with increase in the temperature. From the photoelectrochemical measurements a substantially better enhancement of 472% in terms of photocurrent density was obtained for 300 °C sample at 0 V (vs. RHE) under visible light illumination. These above obtained results indicates the suitability of the CMTS thin films in water splitting applications.